2008
DOI: 10.1536/ihj.49.49
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Pitavastatin, a 3-Hydroxy-3-Methylglutaryl Coenzyme a Reductase Inhibitor, on Cardiac Function in Ischemic and Nonischemic Heart Failure

Abstract: SUMMARYHMG-CoA reductase inhibitors (statins) have recently been reported to improve cardiac function, and decrease the incidence of heart failure (HF) in hyperlipidemic patients. However, evidence for statin treatment in patients with HF remains a subject of debate. Thus, a study was initiated to examine the effects of pitavastatin on cardiac function evaluated by echocardiographic findings and plasma brain natriuretic peptide (BNP) levels in patients with HF. Twenty-three patients with HF were treated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Meanwhile, low-dose statin treatment has been shown to improve left ventricular dysfunction in Japanese patient populations; i.e., Teshima et al [16] and Ohara et al [17] reported that AMI patients benefit from atorvastatin 10 mg/day and pravastatin 10 mg/day, respectively. Furthermore, Aoyagi et al [25] found that pitavastatin 1-2 mg/day is beneficial for treating ischemic heart failure. Their results are consistent with ours in terms of statin type and doses.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, low-dose statin treatment has been shown to improve left ventricular dysfunction in Japanese patient populations; i.e., Teshima et al [16] and Ohara et al [17] reported that AMI patients benefit from atorvastatin 10 mg/day and pravastatin 10 mg/day, respectively. Furthermore, Aoyagi et al [25] found that pitavastatin 1-2 mg/day is beneficial for treating ischemic heart failure. Their results are consistent with ours in terms of statin type and doses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that statins could ameliorate B type natriuretic peptide (BNP) up-regulation (10) and exert a therapeutic effect in myocarditis and postmyocarditis dilated cardiomyopathy (11). Pitavastatin has been reported to exert a preventive effect on pressure overload-induced heart failure (12) and ischemic heart failure (13). However, in a PEARL study (14), pitavastatin did not reduce cardiac death or hospitalization in patients with left ventricular ejection fraction (LVEF) < 30 %.…”
mentioning
confidence: 99%
“…In a small study (n = 23), administration of pitavastatin 1–2 mg/day for 7.5 months significantly increased left ventricular ejection fraction (LVEF) from 42 to 48%, and significantly decreased the plasma brain natriuretic peptide (BNP) level from 94 to 70 pg/mL 107. It has also been reported that there was an inverse correlation between atorvastatin-induced changes in CoQ10 and BNP,108 that CoQ10 level was an independent predictor of mortality in chronic heart failure,109 and that the CoQ10 level in myocardial tissue was lower in patients of NYHA class IV than in patients of NYHA class I 110.…”
Section: Ongoing Pitavastatin Trialsmentioning
confidence: 99%